Current situation and consideration on the seismic science popularization under the environment of media convergence - Ying Zhai; Jianmin Hou; Manfeng Cui (地震科学进展, 2020)
The popularization of seismic science is closely related to the media environment. In recent years, under the environment of media convergence characterized by the depth of network embedding, there has been a new trend in seismic science popularization. Based on personal practical work, this paper summarizes the current work of seismic science popularization under the environment of media convergence, and analyses objectively the strengths and shortages, opportunities and challenges about the seismic science popularization at present. Furthermore, on the basis of conforming to the development trend of the times, this paper thinks deeply about seismic science popularization under the environment of financial media, and provides new methods for the staffs engaged in seismic science popularization works.